Analisis Persepsi Kepuasan Konsumen Terhadap Pemasaran Produk Coklat di Kabupaten Garut - Sutisnawati, Yayah; Sari, Meilina Permata; Putri, Navisa Kusnaedi; Ihsan, Muhamad; Arifin, Fauzi Farhan (JEMBA, 2024)
ABSTRACT The main objective is to find out the impression of buyers towards consumer satisfaction towards chocolate products in Garut Regency. using sampling techniques and using a quantitative approach in its research methodology to collect data by distributing questionnaires to 40 respondents. Using SPSS software analysis tool version 26.0, several multiple linear regression analyses were conducted for this study. Based on the findings, product knowledge and marketing orientation positively affect consumer satisfaction by 63%. This study shows the results that the variables of marketing and product knowledge, when tested using multiple regression analysis, affect consumer satisfaction positively and significantly. This is because chocolate products are well received in terms of product quality and customer service satisfaction. For subsequent researchers who want to conduct research, they can use the findings of this study as a starting point and contribute to the development of stronger and more comprehensive research. In conclusion, this study aims to improve the progress of Garut MSMEs in Indonesia.